Contrasting thermosolvatochromic trends in pyridinium-, pyrrolidinium-, and phosphonium-based ionic liquids - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry B, 2010)
Thermosolvatochromism has been studied in three series of ionic liquids, pyridinium-based 1-butylpyridinium, 1-hexylpyridinium, and 1-octylpyridinium with bis(trifluoromethylsulfonyl)imide [NTf2] and tetrafluoroborate [BF4] anions, pyrrolidinium-based ionic liquids 1-methyl-1-butylpyrrolidium, 1-methyl-1-hexylpyrrolidium, 1-methyl-1-octylpyrrolidium with bis(trifluoromethylsulfonyl) imide anion and phosphonium-based ionic liquids tetrabutylphosphonium with alanate and valinate anions. The effect of increase in alkyl chain length and temperature on normalized polarity E-T(N), Kanilet-Taft parameters, hydrogen bond donor ability (alpha), hydrogen bond acceptor ability (beta), and polarizability (pi*) was investigated in the temperature range of 298-353 K. Interestingly, the polarity decreases with temperature in the case of pyridinium- and pyrrolidinium-based ionic liquids, and it increases with temperature in the case of phosphonium-based ionic liquids.